Analisis Komparatif Sosial, Ekonomi, dan Ekologi antara Komunitas Desa Sawit dan Desa Non Sawit - Tonny, Fredian; Desta Oktarina, Sachnaz; Sipayung, Tungkot; Ulfa Aulia, Risnayanti; Maziah, Lily (Sodality: Jurnal Sosiologi Pedesaan, 2022)
This study aimed to analyze the level of social, economic, and ecological progress of the Oil Palm Village communities and compare the level of social, economic, and ecological progress between the Oil Palm Village and Non-Oil Palm Village communities. Indonesia is one of the major palm oil-producing countries in the world. Palm oil has brought economic benefits nationally and also to local communities. However, in its development, there has been a controversy surrounding the palm oil commodity, namely in the case of Indonesian palm oil which is related to the issues of deforestation and territorialization due to the economic interests of palm oil versus the existence of forest areas. This study used a Quantitative Approach with Secondary Data Methods from primary sources (Ministry of Village, Development of Disadvantage Region, and Transmigration, BPS, and Directorate General of Plantation) with the village communities as the unit of analysis. As many as 524 village communities were selected from the population of Oil Palm Villages and Non-Oil Palm Villages in eight provinces of Indonesia’s oil palm centers with a combination of Purposive Multistage Sampling and Propensity Score Matching methods. Descriptive analysis, comparative analysis, analysis of the difference in progress using the Difference in Difference (DID) model, and the binary logistic regression method were carried out in this study. The results of the study revealed the facts that there has been an increase in social, economic, and ecological progress in various Oil Palm Village communities. The level of social, economic, and ecological progress of Oil Palm Village communities is higher than that of Non-Oil Palm Village communities. These facts indicate that the community sustainability level of the Oil Palm Village communities is superior to that of the Non-Oil Palm Village communities.